Research hotspots and development trends of Brucellar spondylitis in the past 30 years: a bibliometric analysis - Jinyu Wu; Jinyu Wu; Hongxia Yuan; Hongchao Chen (Frontiers in Microbiology)
ObjectiveWith the growing emphasis on global health issues, Brucellar spondylitis, a serious complication of brucellosis, has received increasing attention from researchers. This study employed bibliometric analysis to visually illustrate the scientific advancements and research trends in the field of Brucellar spondylitis research, providing a scientific basis for public health prevention and control strategies.MethodThe data were sourced from the Web of Science Core Collection database, covering the period from January 1, 1984, to December 31, 2023. Network analyses of countries, institutions, authors, and keyword collaborations, as well as co-citation analyses of journals and references, were conducted using CiteSpace software. VOSviewer software was used to analyze the co-occurrence and hotspots of keywords.ResultA total of 246 relevant documents were retrieved, comprising 221 articles and 25 review articles. From 1984 to 2023, the number of research publications exhibited a generally fluctuating upward trend. Turkey and China emerged as the primary contributing countries in this field, with Xinjiang Medical University identified as the most productive research institution. Additionally, Juan D. Colmenero is recognized as the author with the highest number of published articles and citations. “Clinical Infectious Diseases” is regarded as the most influential journal in this domain. Among the 404 keywords analyzed by CiteSpace, the top 10 high-frequency keywords included spondylitis, complication, melitensis, osteoarticular complication, diagnosis, infection, clinical characteristics, epidural abscess, arthritis, and feature. A total of 14 clusters were formed. In the burst analysis of the top 15 keywords, “instrumentation” exhibited the highest burst intensity, while “arthritis” demonstrated the longest burst duration. Emerging keywords include “experience,” “ankylosing spondylitis,” “China,” and “instrumentation.”ConclusionThis study is the first bibliometric analysis in the field of Brucellar spondylitis, which revealed that the research hotspots in this field included the clinical characteristics of the disease, the management of complications, and treatment strategies. The development trend may involve enhancements in early diagnostic methods and advancements in surgical instruments. This study serves as a valuable reference for future research directions.